Studies on intra-individual variability of selected cross-country skiing techniques - Babiel, S. (European Journal of Sport Science, 2003)
The aim of this study was to define intra-individual variability and to mark this "range", thus enabling us to distinguish variability from differences in tech nique. The focus of this paper was the description of intra-individual variability in reaction forces and derived parameters. A skier performed ski techniques within nearly constant external conditions over the course of many trials. Time parameters for both ski and pole can be regarded as constant, but there are variations in the distribution in ball and heel force, especially in the phase of poling. For some derived parameters, we cannot interpret the isolated ski parameter but must consider the poles. Measurement economy becomes very important, and caution must be exercised in diagnosing the technique in only a few trials. As described above, there is, among those with greater skill, only a slight variability among selected parameters; therefore, data collection can be reduced to a few trials. This will lead to greater economy in cross-country skiing research and will help to identify an athlete's individual technique. We also can quantify the different realizations of the same technique by several athletes by the use of a force-time curve.